2010
DOI: 10.1111/j.1601-183x.2010.00612.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain gene expression in relation to fearfulness in female red junglefowl (Gallus gallus)

Abstract: The biology of fear is central to animal welfare and has been a major target for selection during domestication. Fear responses were studied in female red junglefowl (RJF), the ancestor of domesticated chickens. A total of 31 females were tested in a ground predator test, an aerial predator test and a tonic immobility (TI) test, in order to assess their level of fearfulness across different situations. Two to six variables from each test were entered into a principal component (PC) analysis, which showed one m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 39 publications
(52 reference statements)
1
20
1
Order By: Relevance
“…It controls the timing and intensity of gene expression and therefore is crucial to understanding phenotypic differences between populations. As behavioural variation often correlates with variation in gene expression (Hofmann, 2003;Jöngren et al, 2010), epigenetic mechanisms should be important in behaviour regulation as well. However, the research area is still novel, and relatively unexplored.…”
Section: Epigenetic Mechanisms: What Causes Differences In Gene Exprementioning
confidence: 99%
“…It controls the timing and intensity of gene expression and therefore is crucial to understanding phenotypic differences between populations. As behavioural variation often correlates with variation in gene expression (Hofmann, 2003;Jöngren et al, 2010), epigenetic mechanisms should be important in behaviour regulation as well. However, the research area is still novel, and relatively unexplored.…”
Section: Epigenetic Mechanisms: What Causes Differences In Gene Exprementioning
confidence: 99%
“…The fear tests used in this study are frequently used in chicken research and are considered to assess fear (Campler et al 2009;Jensen 2005, 2008;Jöngren et al 2010). In an earlier study, Jöngren et al (2010) exposed Red Junglefowl females to similar fear tests and found two major components explaining 48.4% of the variance in a PCA.…”
Section: The Domestic Phenotypementioning
confidence: 85%
“…In an earlier study, Jöngren et al (2010) exposed Red Junglefowl females to similar fear tests and found two major components explaining 48.4% of the variance in a PCA. The first component was interpreted as a general fear factor whereas the second was mainly explained by TI.…”
Section: The Domestic Phenotypementioning
confidence: 92%
“…Egg layers show altered and less extreme antipredatory behavior, and fear related behaviors in the chicken have been reduced, maybe as the co-existence with humans has relaxed the natural selection pressure of predation [71,72]. Transmission of behavioral differences over generations has been shown to have underlying genetic components [73,74], as do differences in fear within populations [75].…”
Section: From Wild To Domestic Chickenmentioning
confidence: 99%